Pengembangan sistem informasi Posyandu berbasis notifikasi SMS gateway - Taurusta, Cindy; Suryawinata, Mohammad; Rosyidah, Rafhani (Universitas Negeri Yogyakarta, 2023)
Posyandu RW.05 Pondok Manggala is a Posyandu that overshadow the mothers who have a toddler in Balas Klumprik Village Surabaya. Where the entire system from registration to information about counseling, immunization, and visits and routine checks by health officers Reply Klumprik still done manually. The intended manual here is that the delivery is still through the mouth, and the data collection was still with the book. So that becomes an obstacle for the mothers of posyandu cadres here who have difficulties informing, reminding, monitoring, and socializing everything related to activities in Posyandu. Some babies/toddlers have malnutrition are not monitored regularly, only known when the mother and toddler come to posyandu. Therefore, a Posyandu Information System for Klasrik Balas Village was established to help Posyandu cadres in informing, socializing, reminding, and monitoring the development of mothers and their babies who are members of Posyandu RW.05 Pondok Manggala Surabaya.